Post-operative cosmesis of autologous capsular patch grafts in tube shunt surgery: Case series of 18 eyes - Lauren Ciulla; Jessie Wang; Mary Qiu (American Journal of Ophthalmology Case Reports)
Background: Capsule tissue from preexisting tube shunts can be used as autologous patch grafts in patients that require tube revision, exchange, or removal. Purpose: To retrospectively describe the use of autologous capsular patch grafts for tube shunt surgeries and demonstrate their cosmetic outcomes. Methods: Tube shunt surgeries using autologous capsular patch grafts from March 2, 2020 through August 10, 2023 by a single surgeon at the University of Chicago were included in this case series. Results: 18 patients had capsule patch grafts during tube shunt surgeries. 16 patients have post-operative photos available. 18 patients had capsule patch grafts during tube shunt surgeries. 16 patients have post-operative photos available. There were 2 cases of failed superotemporal tube shunts for which a second inferonasal tube was placed. There were 9 cases of same-quadrant Ahmed FP7 to BGI-350 exchange: 7 for uncontrolled IOP, 2 for tube erosion. There were also five cases of same-quadrant exchange with varying tube types for indications such as erosion, hypotony, and elevated intra-ocular pressure. There was also one case of different quadrant exchange for impending endothelial keratoplasty for corneal failure and poor cosmesis of the tube. Finally, there was one case of tube shunt removal for erosion with goniotomy. Duration of post-operative follow-up averaged 57 weeks (range 2–178 weeks). There were no complications related to the autografts. Conclusion: Autologous capsular patch grafts can be efficacious in tube shunt surgeries with good cosmetic outcome. Longer follow up and larger trials are needed.